2020
DOI: 10.1113/ep088515
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prefrontal cerebral oxygenation and microvascular blood volume in hypoxia and possible association with acute mountain sickness

Abstract: The aim of this study was to evaluate changes in prefrontal cerebral oxygenation and microvascular blood volume during exercise in normobaric hypoxia and to investigate possible associations with the occurrence of acute mountain sickness (AMS) at altitude. Twenty-two healthy individuals (age, 26 ± 4 years; peak oxygen uptake, 42 ± 4 ml kg −1 min −1) were tested in two different conditions: normoxia (NORM) and normobaric hypoxia (fraction of inspired O 2 = 0.13; HYPO). Data were collected at rest and during sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Furthermore, we found that the polymorphism of the Apolipoprotein H ( APOH ) gene is associated with elevated levels of lipoprotein (a), an independent risk factor for cardiovascular disease [ 43 ]. The incidence of ischemic cardiovascular and cerebrovascular diseases is significantly higher in high-altitude and hypoxic areas compared to plain areas [ 44 , 45 , 46 , 47 ]. Fatty acid-binding protein 4 (FABP4) is a lipid-binding protein that belongs to the intracellular family.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the polymorphism of the Apolipoprotein H ( APOH ) gene is associated with elevated levels of lipoprotein (a), an independent risk factor for cardiovascular disease [ 43 ]. The incidence of ischemic cardiovascular and cerebrovascular diseases is significantly higher in high-altitude and hypoxic areas compared to plain areas [ 44 , 45 , 46 , 47 ]. Fatty acid-binding protein 4 (FABP4) is a lipid-binding protein that belongs to the intracellular family.…”
Section: Discussionmentioning
confidence: 99%
“…Further, cognitive processes associated with the best visuo-spatial abilities (i.e., neural efficiency) could be unveiled by fNIRS in the brain of highly skilled aerobatic pilots and Formula One race-car professional drivers. Finally, assessing cortical activation and tracking cerebral oxygenation changes during ascent and stay at high altitude environments may inform both on the neural correlates of cognitive control (Davranche et al, 2016 ; Champigneulle et al, 2022 ) and in the pathogenesis of acute mountain sickness (Manferdelli et al, 2021 ), respectively.…”
Section: Current Use Of Cerebral Nirs During Sportsmentioning
confidence: 99%
“…The cardiovascular system is highly oxygen- and energy-consuming and is sensitive to hypoxia. In particular, the cardiovascular system is affected by oxidative stress, sympathetic nerve excitation, and other mechanisms in high-altitude hypoxic environments, resulting in several physiological and pathological changes [ 3 , 4 , 5 , 6 ]. Studies have shown that altitude and the prevalence of hypertension are positively correlated.…”
Section: Introductionmentioning
confidence: 99%